Commuter Travel Pattern to OUSL Nawala: A Case Study - L.M. Prathapasinghe; D.B. Maddumaarachchi; G.N. Damayanthi; K.S. Weerasekera (The Open University of Sri Lanka, 2019)
This study intends to analyse the inflow pattern of commuters of OUSL Colombo Regional Center and Main University Nawala with their travel origins, and study their travel-mode patterns and travel nature. The study followed road side interviews, which was the most suitable method to be adopted for such study purpose. This was identified by an extensive literature survey. Pilot studies were conducted during midweek and weekends to identify the volume of walkers and motorists coming through the four gates of the university to get an idea on size of survey teams to conduct interviews and to decide how to locate survey teams around the entry gates during the main surveys. Main surveys were carried out on a Saturday (weekend) and a Wednesday (midweek), from 8:00 to 18:00 hours covering a 10-hour survey duration. According to the questionnaire, the walkers and motorists coming to OUSL through all four gates were interviewed and contacted more than 1000 respondents. This survey has captured around 58% of total arrivals during the weekend and 56% during midweek. It was observed that a total of 51% of university community came through Nugegoda. Most of them came from Kotte Divisional Secretaries division (zone no 7). It was observed that from the total arrivals, 82 % (weekend) and 66% (midweek) came from zone 7. Out of the community coming to the University for Study Purposes during weekends, 51% were males and 48% females; during midweek, 54% were males and 46% females. Around 74% of community coming to OUSL use buses, while 9% come by trains. As the final outcome of this study, a shuttle service of buses was designed to provide a better service to OUSL visitors during the rush hours (ie. 8:00 am to 10:00 pm). Shuttle services are proposed from some main towns. Through the study it was found that presently no adequate number of passengers use trains.